2014
DOI: 10.3389/fpsyg.2014.00675
|View full text |Cite
|
Sign up to set email alerts
|

Development of magnitude processing in children with developmental dyscalculia: space, time, and number

Abstract: Developmental dyscalculia (DD) is a learning disorder associated with impairments in a preverbal non-symbolic approximate number system (ANS) pertaining to areas in and around the intraparietal sulcus (IPS). The current study sought to enhance our understanding of the developmental trajectory of the ANS and symbolic number processing skills, thereby getting insight into whether a deficit in the ANS precedes or is preceded by impaired symbolic and exact number processing. Recent work has also suggested that hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
59
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 82 publications
(181 reference statements)
11
59
4
Order By: Relevance
“…(Skagerlund and Träff, 2014) results were also in accordance with Feigenson (2007), who suggested that if the diverse magnitude representations share a common mechanism, deficits in one dimension should be paralleled by deficits in other magnitude processing abilities. This led Skagerlund and Träff (2014) to suggest that children with DD, whose primary deficit was thought to be circumscribed to the ANS prior to the study, may in fact suffer from a more comprehensive magnitude processing deficit that extends from quantity processing to also include processing of time and space.…”
Section: Core Hypotheses Regarding Ddsupporting
confidence: 80%
See 3 more Smart Citations
“…(Skagerlund and Träff, 2014) results were also in accordance with Feigenson (2007), who suggested that if the diverse magnitude representations share a common mechanism, deficits in one dimension should be paralleled by deficits in other magnitude processing abilities. This led Skagerlund and Träff (2014) to suggest that children with DD, whose primary deficit was thought to be circumscribed to the ANS prior to the study, may in fact suffer from a more comprehensive magnitude processing deficit that extends from quantity processing to also include processing of time and space.…”
Section: Core Hypotheses Regarding Ddsupporting
confidence: 80%
“…Recent studies indicate that children with DD or mathematical difficulties not only have number processing deficits but also problems in processing other magnitudes such as time and space (Ashkenazi and Henik, 2010; Vicario et al, 2012; Moll et al, 2014; Skagerlund and Träff, 2014). For example, Skagerlund and Träff (2014) found that 10-years olds with DD showed impaired ANS acuity (i.e., non-symbolic number discrimination), but also problems with time discrimination and difficulties with two spatial skills; spatial visualization (paper-folding) and mental rotation.…”
Section: Core Hypotheses Regarding Ddmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study, in fact, showed that typically developing individuals with difficulties in learning mathematics have impaired ability not only in comparing numerosities, but also in comparing continuous quantities like time (Skagerlund & Trä ff, 2014). Such deficits have not been reported in the case of individuals with DS.…”
Section: Discussion and General Conclusionmentioning
confidence: 97%